1045 Impact Of Pre-treatment Sleep And Menopausal Status On Sleep Quality In The 12 Months Following A Breast Cancer Diagnosis. (27th May 2020) - Squires, L; Mahon, K; Rash, J; Powell, E; Seal, M; Garland, S N
Abstract: Introduction: Sleep disturbances are a prevalent and enduring problem in women who have completed treatment for breast cancer. Less is known about whether sleep during and after cancer treatment is influenced by pre-treatment sleep quality and menopausal status. The present study aims to examine the trajectory of sleep quality in the 12 months following a cancer diagnosis and assess whether trajectory is influenced by pre-treatment sleep quality and menopausal status. Methods: Newly-diagnosed women (N=88) with non-metastatic BCa were recruited before beginning treatment. They completed the Pittsburgh Sleep Quality Index (PSQI) before treatment and 4, 8, and 12 months later. Women with a score ≥5 on the Pittsburgh Sleep Quality Index at treatment onset were classified as poor sleepers. Menopausal status (pre- or post-menopausal) was chart abstracted. A mixed ANOVA assessed the impact of pre-treatment sleep quality and menopausal status on sleep quality trajectory. Results: The mean age of the sample was 60 years, 70% were classified as poor sleepers, and 72% were post-menopausal. There was a significant linear time by sleep quality interaction, F(1, 83)= 5.79, p =.02. Good sleepers experienced a greater initial worsening of sleep quality than poor sleepers. At 12 months, poor sleepers had returned to baseline levels whereas scores in good sleepers remained higher than baseline. The 3-way time x sleep quality x menopausal status and the 2-way time by menopausal status interactions were not significant. Conclusion: Baseline sleep quality is a more powerful determinant of sleep trajectory during treatment than menopausal status. Early intervention is necessary to treat existing sleep problems and prevent the development of sleep problems in women with a history of good sleep. Support: Dr. Garland is supported by a New Investigator Award and seed funding from the Beatrice Hunter Cancer Research Institute (BHCRI).